Congestion in historical city centres – discussion on phenomena and analysis with network thinking methodology and grey sets theory - Ragin-Skorecka, Katarzyna; Stachowiak, Agnieszka; Wojciechowski, Hubert; Fertsch, Marek (Kongestia w historycznych dzielnicach Poznania – charakterystyka zjawiska z wykorzystaniem metodyki myślenia sieciowego i zbiorów szarych, 2019)
Congestion is the result of the accumulation of flows of different nature (i.e. people, goods, waste) in cities, which on the one hand results from their development, the consequence of which is the intensification of flows, on the other is also an example of the main barrier to the functioning and development of cities. This problem defined the purpose of the study and the article which is to characterize the phenomenon of congestion and to identify the structure of this issue, so as to deliberately define actions to alleviate congestion and its negative effects. The aim of the study was achieved using network thinking methodology, based on the knowledge of the appointed expert group. The test results were processed using grey collections and arithmetic. Research methodology was justified by the complexity and multi-faceted nature of the research problem. The research results indicated the potential of shared transport, and thus the importance of ICT, and above all mobile apps in reducing congestion in historical city districts
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 3 (53), s. 86-96
Keywords: city logistics; congestion; grey system theory; systemic thinking; logistyka miejska; kongestia; teoria zbiorów szarych; metodyka myślenia systemowego